Sidelobe Reduction in Linear and Planar Array Antenna Using the Genetic Algorithm - Noaman, Ali Abdulhadi; Abdallah, Abdul Kareem S.; Ali, Ramzy S. (Basrah Journal for Engineering Sciences, 2010)
This paper describes the problem of minimizing-the sidelobe levels in the radiation pattern of antenna arrays by using the genetic algorithm. Two types of genetic algorithms representation are used here:., binaiy and continuous genetic algorithms depending on the nature of the problem at hand. Adaptive genetic algorithm wnich is a special type of genetic algorithm is used in this work. The obtained results explain the capability of this approach to obtain the desired sidelobe level.